Synergistic protective effects of TCM formula NRICM102 and N-acetylcysteine against hepatorenal injury in a mouse model of bongkrekic acid poisoning - Shen, Yuh-Chiang; Wang, Yea-Hwey; Liou, Kuo-Tong; Wei, Wen-Chi; Cheng, Jing-Jy; Liu, Hui-Kang; Huang, Nai-Kuei; Lo, I-Wen; Chang, Cher-Chia; Chiou, Wen-Fei; Tsai, Keng-Chang; Chiou, Chun-Tang; et al. (Frontiers in Pharmacology, 2025)
Bongkrekic acid (BKA), a mitochondrial toxin produced by Burkholderia cocovenenans subsp. farinofermentans, is typically found in contaminated fermented rice products such as tempeh bongkrek, causing severe foodborne illnesses marked by systemic inflammation, multi-organ failure (MOF), and high mortality rates (40%–100%). A recent outbreak in Taiwan (2024) resulted in six fatalities among 33 affected individuals, underscoring the urgent clinical need for effective treatments. This study evaluated the therapeutic potential of NRICM102, a novel traditional Chinese medicine (TCM) formulation, combined with the antioxidant N-acetylcysteine (NAC), against BKA-induced hepatorenal toxicity in a mouse model. NRICM102 (1.5–3.0 g/kg), NAC (0.5 g/kg), and their combination significantly improved survival, reduced serum biomarkers (GOT, GPT, BUN), and alleviated liver and kidney histopathological damage following acute (5.0 mg/kg) and subacute (2.0 mg/kg) BKA exposure. RNA-seq analyses suggested that the NRICM102-NAC combination synergistically modulated critical pathways, including mitochondrial function, cytochrome P450 enzyme activity, oxidative stress, immune responses, and cell death regulation. Despite these promising findings, mechanistic conclusions remain associative and require further validation using targeted mitochondrial studies. Collectively, NRICM102 combined with NAC offers a promising, translationally relevant therapeutic strategy warranting additional preclinical safety and pharmacokinetic assessments to advance toward clinical application.